(untitled) (Universal International Scientific Journal, 2026)
This article examines the growing role of artificial intelligence (AI) in teaching English as a foreign language (EFL). With the rapid development of digital technologies, AI has become an important tool in modern education. The study focuses on how artificial intelligence supports English language teaching by enhancing grammar, vocabulary, reading, and writing skills. Additionally, the article highlights the advantages and challenges of integrating AI into EFL classrooms and emphasizes the importance of using AI as a supplementary tool rather than a replacement for teachers. The findings suggest that AI can significantly improve the quality and effectiveness of EFL instruction when used appropriately.